Reorientation of the Criminal Justice System Towards Restorative Justice in The Perspective of the New Criminal Code (KUHP) - Juri Kasvarof (CV. Publikasi Indonesia, 2026)
The reform of criminal law through Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code) marks a paradigm shift in the Indonesian criminal justice system—from a retributive approach to a more humanistic and corrective one. This article aims to analyze the reorientation of the criminal justice system towards restorative justice from the perspective of the New Criminal Code, by placing the values of restoration, balance, and humanity as the main cornerstones of criminalization. In contrast to previous research, which generally positions restorative justice as limited to sectoral law enforcement policies or the discretion of the apparatus, this article emphasizes that the New Criminal Code has integrated the principles of restorative justice both normatively and structurally into the national criminal law system. The analysis was carried out using a normative and conceptual juridical approach to the purpose of punishment, sentencing guidelines, and the role of judges in imposing sentences, as stipulated in the New Criminal Code, and by comparing these with conventional criminal justice practices. The results of the study show that the New Criminal Code not only accommodates restorative justice as an alternative mechanism for case resolution but also establishes it as a philosophical orientation for the criminal justice system, which has implications for changing the perspectives of perpetrators, victims, and society. Thus, this reorientation requires consistent implementation by law enforcement officials so that the goals of criminal law reform can be achieved substantively.